Optimization of educational activities of departments of morphological profile of Zaporizhzhya State Medical and Pharmaceutical University - Zviahina, H. O.; Pototska, O. I.; Kirsanova, O. V.; Makyeyeva, L. V.; Звягіна, Ганна Олександрівна; Потоцька, Олена Іванівна; Кірсанова, Олена Валентинівна; Макєєва, Людмила Валеріївна (My University, 2023)
The process of optimizing educational activities as a phenomenon that allows to achieve maximum results with minimal time expenditure is a widely used phenomenon in various fields of science. It has been used in pedagogy since the last century. But forms and methods of optimization constantly need improvement and selection depending on the specific learning situation. Objective. Departments of morphological profile working with students of the 1st-2nd year of medical universities during the martial law have developed their optimal teaching methods. It was their activity that formed the basis of our research. Methods. Among the methods used by us in the article, there are theoretical ones - the descent from the abstract to the concrete, complex ones - practical direction - analysis, synthesis, induction; among special ‒ component analysis. Results. Application of the principle of optimality allows balancing all elements of the educational process. Such work has several main stages, such as: assessment of the state of the existing educational process; selection of the goal and tasks of optimization; selection of forms and methods of conducting lectures, practical classes, current and intermediate control, making corrections according to the goal. And, of course, evaluating the results from the point of view of the optimality of the time used and the efforts made. Therefore, organizational forms of work in the learning process can be adjusted. The methodical and educational materials used must correspond to the training program, be informative, logical and consistent. Only such materials will successfully complement the technical means of ensuring the educational process. Modern technologies, such as the Anatomage anatomical table, 3D Ogranon Anatomy VR, virtual laboratory simulator "Labster" play a major role in optimizing the learning process. Conclusion. Optimization of educational activities at departments of morphological profile of Zaporizhzhya State Medical and Pharmaceutical University is carried out systematically and continuously. Distance learning, which was implemented during the martial law, forced to review the forms and methods of optimization that were used in the learning process. Therefore, the improvement of the existing and the development of new methods of optimizing the educational process at the departments of morphological profile will constantly change according to the circumstances. Процес оптимізації навчальної діяльності як явище, що дає можливість досягати максимальних результатів при мінімальних витратах часу є широко застосовуваним явищем у різних галузях наук. Саме у педагогіці він застосовується ще з минулого століття. Але форми і методи оптимізації постійно потребують удосконалення і відбору залежно від конкретної ситуації навчання. Мета. Кафедри морфологічного профілю, що працюють зі студентами 1-2 курсу медичних університетів під час військового стану виробили свої оптимальні методи навчання. Саме їх діяльність лягла в основу нашого дослідження. Методи. Серед використаних нами у статті методів присутні як теоретичні – сходження від абстрактного до конкретного, комплексні – практичного спрямування – аналізу, синтезу, індукції; серед спеціальних ‒ компонентного аналізу. Результати. Застосування принципу оптимальності дозволяє збалансовувати усі елементи навчального процесу. Така робота має декілька основних етапів, таких як: оцінювання стану існуючого освітнього процесу; виділення мети та завдань оптимізації; вибір форм і методів проведення лекційних, практичних занять, поточного та проміжного контролю, внесення коректив відповідно до мети. І, звісно, оцінювання результатів з точки зору оптимальності використаного часу і докладених зусиль. Тож організаційні форми роботи в процесі навчання можуть бути скориговані. Використані методичні та навчальні матеріали мають відповідати програмі навчання, бути інформативними, логічними та послідовними. Лише такі матеріали вдало доповнять технічні засоби забезпечення навчального процесу. Велику роль в оптимізації процесу навчання відіграють сучасні технології, такі як анатомічний стіл Аnatomage, 3D Ogranon Anatomy VR, симулятор віртуальних лабораторій «Labster». Підсумок. Оптимізація навчальної діяльності на кафедрах морфологічного профілю Запорізького державного медико-фармацевтичного університету проводиться системно і постійно. Дистанційне навчання, яке було впроваджене під час військового стану, примусило переглянути форми і методи оптимізації, які були використані в процесі навчання. Тож вдосконалення існуючих та напрацювання нових методів оптимізації навчального процесу на кафедрах морфологічного профілю постійно змінюватиметься відповідно до обставин.
Оптимізація навчальної діяльності кафедр морфологічного профілю Запорізького державного медико-фармацевтичного університету
Zviahina H. O. - 0000-0002-9778-6833; Pototska O. I. - 0000-0002-7635-5129; Kirsanova O. V. - 0000-0001-5337-2439; Makyeyeva L. V. - 0000-0002-3188-2638.
Keywords: optimization; optimality principle; morphological profile; optimality criteria; оптимізація; принцип оптимальності; морфологічний профіль; критерії оптимальності